Case report: Disseminated Mycobacterium tuberculosis infection in a dog - Martinho, Anna Paula Vitirito [UNESP]; Franco, Marília Masello Junqueira [UNESP]; Ribeiro, Márcio Garcia [UNESP]; Perrotti, Isabella Belletti Mutt [UNESP]; Mangia, Simone Henriques [UNESP]; Megid, Jane [UNESP]; Vulcano, Luiz Carlos [UNESP]; Lara, Gustavo Henrique Batista [UNESP]; Santos, Adolfo Carlos Barreto [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Sanches, Osimar de Carvalho; Paes, Antonio Carlos [UNESP] (American Society of Tropical Medicine and Hygiene, 2013)
An uncommon disseminated Mycobacterium tuberculosis infection is described in a 12-year-old female dog presenting with fever, dyspnea, cough, weight loss, lymphadenopathy, melena, epistaxis, and emesis. The dog had a history of close contact with its owner, who died of pulmonary tuberculosis. Radiographic examination revealed diffuse radio-opaque images in both lung lobes, diffuse visible masses in abdominal organs, and hilar and mesenteric lymphadenopathy. Bronchial washing samples and feces were negative for acid-fast organisms. Polymerase chain reaction (PCR)-based species identification of bronchial washing samples, feces, and urine revealed M. tuberculosis using PCR-restriction enzyme pattern analysis-PRA. Because of public health concerns, which were worsened by the physical condition of the dog, euthanasia of the animal was recommended. Rough and tough colonies suggestive of M. tuberculosis were observed after microbiological culture of lung, liver, spleen, heart, and lymph node fragments in Löwenstein-Jensen and Stonebrink media. The PRA analysis enabled diagnosis of M. tuberculosis strains isolated from organs. Copyright © 2013 by The American Society of Tropical Medicine and Hygiene.
Keywords: alanine aminotransferase; alkaline phosphatase; isoniazid; pyrazinamide; rifampicin; antibiotic therapy; bacterial strain; bacterium culture; clinical protocol; coughing; dog disease; dyspnea; epistaxis; euthanasia; female; histopathology; lung tuberculosis; lymphadenopathy; melena; nonhuman; phenotype; respiratory distress; thorax radiography; tuberculosis; vomiting; weight reduction; animal; animal disease; case report; dog; feces; isolation and purification; lung; lung lavage; methodology; microbiology; Mycobacterium tuberculosis; pathology; polymerase chain reaction; urine; Animals; Bronchoalveolar Lavage Fluid; Dog Diseases; Dogs; Feces; Female; Lung; Polymerase Chain Reaction; Tuberculosis